Scholastic Ethics in Lithuania - Plečkaitis, Romanas (Problemos, 1968)
Moral philosophy, or ethics, was the last part of the course of scholastic philosophy. Sometimes it was taught all through the academic year and sometimes it was not taught at all. Ethics was taught in accordance with Aristotle, supplementing the course with the theories of the prominent authorities both of the Middle Ages and the so called second scholasticism. Ethics was understood as a theory of individual behaviour. It was assumed that theology did not deny ethics. Happiness can be attained by a man only through moral life the rules of which are dictated by ethics. Physical good and spiritual good are clearly contrasted, good being understood as contemplation of the truth. Scholasticism was not concerned with the social content of ethical values. Moral features common to all mankind were presented in an abstract way, ignoring the spirit of the time and the reality of the l7th and the beginning of the l8th century.